(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Learning a second or foreign language has some difficulties the first time after the day young learners try memorize each of the new words as well as new learners can improve their mention skill with memorize a lot of words. The article is about some problems in teaching vocabulary to young learners.